The return of serve - Klein, H. (coachesinfo.com)
As a feature of biomechanics, kinematic analysis delivers information about invisible aspects of human movement co-ordination. Such analysis is intended to support the trainer's eye with precise information in the difficult task of identifying mistakes and finding out appropriate solutions. By using high-speed cameras operating at 200 to 400 frames per second, coaches can also gain information about the total time budget of the return and the quality of the impact on the racket. Content of the article: - Introduction - The Research - Applied Finding for Coaches - Summary Summary: On the basis of these recent research efforts it is highly recommended to - train anticipatory abilities; - train returns by varying the time pressure imposed on the players in order to improve their time management; - offer tasks for reprogramming (e.g. backhand to forehand return) and; - work to control impact location on the racket.